2008
DOI: 10.1002/ptr.2538
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Sanionia uncinata, a polar moss species from King George Island, Antarctica

Abstract: Antioxidant agents counter reactive oxygen species (ROS) and can be used in cosmetic and medicinal applications. The goal of this study was to evaluate the antioxidant activity of an Antarctic moss species from King George Island (Antarctica), tentatively designated as KSJ-M5. On the basis of morphological characteristics, KSJ-M5 was identified as Sanionia uncinata (Hedw.) Loeske (Amblystegiaceae). The identification was confirmed by comparing the partial sequence of the ITS (internal transcribed spacer) regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
(20 reference statements)
0
17
0
8
Order By: Relevance
“…To estimate the antioxidant potential of plant extracts, DPPH (1, 1-diphenyl-2-picrylhydrazyl) reducing activity was assayed as described previously [11, 12]. Similarly, antimicrobial activity was assayed by disk diffusion method [13] against human pathogenic microorganisms, Staphylococcus aureus , Escherichia coli , Candida albicans and Aspergillus niger .…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the antioxidant potential of plant extracts, DPPH (1, 1-diphenyl-2-picrylhydrazyl) reducing activity was assayed as described previously [11, 12]. Similarly, antimicrobial activity was assayed by disk diffusion method [13] against human pathogenic microorganisms, Staphylococcus aureus , Escherichia coli , Candida albicans and Aspergillus niger .…”
Section: Methodsmentioning
confidence: 99%
“…Hari Datta et al 5 reported Sanionia uncinata a polar moss as an important source of natural antioxidant agents and Boris pejin et al 6 reported the moss Bryum moravicum possess potential antioxidant activity. Similarly, the ethanolic extracts of Atrichum undulatum, Polythrichum formosum (Polytrichaceae) possess stronger antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…But natural antioxidants, especially phenolics and fl avonoids from tea, wine, fruits, vegetables and spices are already exploited commercially either as antioxidant additives or as nutritional supplements. Also many other plant species have been investigated in the search for novel antioxidants (Koleva et al, 2002;Mantle et al, 2000;Oke & Hamburger, 2002;Bhattarai et al, 2008), but generally there is still a demand to fi nd more information concerning the antioxidant potential of plant species as they are safe and also bioactive.…”
Section: Introductionmentioning
confidence: 99%